2012
DOI: 10.1152/ajpheart.00463.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elastin degradation and surrounding matrix support on artery stability

Abstract: Tortuous arteries are often associated with aging, hypertension, atherosclerosis, and degenerative vascular diseases, but the mechanisms are poorly understood. Our recent theoretical analysis suggested that mechanical instability (buckling) may lead to tortuous blood vessels. The objectives of this study were to determine the critical pressure of artery buckling and the effects of elastin degradation and surrounding matrix support on the mechanical stability of arteries. The mechanical properties and critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
126
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(136 citation statements)
references
References 56 publications
10
126
0
Order By: Relevance
“…Disease and ageing, however, alter the respective compositions, leading to often undesirable changes in function. Ageing has been shown to cause a loss of medial elastin followed by an increase in the stiffer collagen fibres, further stiffened by additional cross-linking, to compensate [8,9,10,11]. This results in the elastin-collagen interaction altering and the stiffer collagen fibres being recruited at smaller deformations, leading to an observed stiffening of the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…Disease and ageing, however, alter the respective compositions, leading to often undesirable changes in function. Ageing has been shown to cause a loss of medial elastin followed by an increase in the stiffer collagen fibres, further stiffened by additional cross-linking, to compensate [8,9,10,11]. This results in the elastin-collagen interaction altering and the stiffer collagen fibres being recruited at smaller deformations, leading to an observed stiffening of the arterial wall.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental studies have shown that artery buckling occurs under both static pressure and pulsatile flow conditions [1,[13][14][15][16][17]. The critical buckling pressure depends on vessel wall dimensions, material properties, axial stretch ratio, and surrounding matrix support [1,3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The critical buckling pressure depends on vessel wall dimensions, material properties, axial stretch ratio, and surrounding matrix support [1,3,16,17]. However, it remains unclear how the buckling behavior of arteries under pulsatile flow differs from the buckling behavior under static pressure or steadystate flow.…”
Section: Introductionmentioning
confidence: 99%
“…In Fung, 90 the stretch ratio in rabbit arteries varies from 1.6 in the carotid to 1.4 for the upper abdominal aorta, whereas Fung and Liu 91 showed that the opening angle in normal rats varies from 160° in the ascending aorta and 90° in the arch to 60° in the thoracic region. Details of the use of these parameters for the modeling of the vessel properties are not discussed here, but the reader can refer to Lee et al, 92 Holzapfel et al, 93 or Raghavan et al 94 for additional information on this issue. Concerning the variation of the elastic properties as a function of the load applied (pressure, tension, and flow, for instance), one can refer to Martinez et al 95 and Lee et al 92 In these papers, the authors measure the evolution of the longitudinal and circumferential stretch ratio as a function of internal pressure during an inflation test.…”
Section: Solid Physical Propertiesmentioning
confidence: 99%
“…Details of the use of these parameters for the modeling of the vessel properties are not discussed here, but the reader can refer to Lee et al, 92 Holzapfel et al, 93 or Raghavan et al 94 for additional information on this issue. Concerning the variation of the elastic properties as a function of the load applied (pressure, tension, and flow, for instance), one can refer to Martinez et al 95 and Lee et al 92 In these papers, the authors measure the evolution of the longitudinal and circumferential stretch ratio as a function of internal pressure during an inflation test. This procedure enables them to approximate the stress-strain evolution, characteristic of the elastic properties of a material, by a mathematical hyperelastic model.…”
Section: Solid Physical Propertiesmentioning
confidence: 99%